Microalgae Pediastrum boryanum enhances growth and modulates physiology and transcriptome in Nile tilapia - Raghad E. Soliman; Ahmed Ateya; Mohamed Abou-El-Atta; Wasseem Emam; Mohamed M. Abdel-Rahim; Ashraf I. G. Elhetawy; Ahmed E. Elshafey; Radi A. Mohamed (Scientific Reports)
Abstract The study aimed to explore the impact of dietary Pediastrum boryanum (PB) on growth performance, immune-physiological and transcriptome responses of Nile tilapia (Oreochromis niloticus). A 90-day trial using 1800 fish (17.00 ± 1.722 g) was allocated at random into 4 groups, three replicates each. The 4 groups received PB at 0 (G1), 1 (G2), 2 (G3), and 4 (G4) g/kg diet, respectively. The fish in Group G3 displayed a significant (p < 0.05) increase in final body weight, weight gain, specific growth rate, and final length when compared to the control group. In addition, red blood cell counts (RBCs), and neutrophils were significantly (p < 0.05) higher in G3. The groups’ biochemical parameters did not significantly differ from one another; nevertheless, significant (p < 0.05) variations in immunoglobulin M (IgM), phagocytic activity, and the values of the phagocytic index. The antioxidative activity of superoxide dismutase (SOD) and catalase differed significantly (p < 0.05) between groups, with the highest values seen in group G3. Moreover, there was a significant (p < 0.05) upgrade in the expression levels of GH, IGF-1, SOD, catalase, IL-6, IL-8, and PGAM2 genes in group G3. Additionally, G3 had the most typical liver structure, significantly (p < 0.05) increased villi length and width, and a thicker lamina propria in the intestine. In conclusion, dietary supplementation of PB boosted growth performance, blood and serum profile, morphometric evaluation of the liver and intestine, and expression of genes related to growth, antioxidant capacity, immunity, and energy metabolism in Nile tilapia.